Tradisi Ter-ater di Kalangan Masyarakat Madura - Musthafa, Fera Andriani Djakfar; Hafsin, Achmad (Proceedings of Annual Conference for Muslim Scholars, 2025)
Ter-ater is a preserved tradition in Madura, namely the custom of delivering food to neighbours or relatives at certain moments, with certain types of dishes as a representation of local wisdom adapted to Islamic values. This study aims to describe the internalization of Islamic values contained in the ter-ater, such as friendship, social concern, and the spirit of sharing, as well as its impact on strengthening social harmony through elements of trust, reciprocity, and social networks among multicultural communities. This study uses a qualitative approach with an ethnographic study method in the urban community of Bangkalan, particularly the residents of Bangkalan Indah, Mlajah Village, Bangkalan District, which has religious and ethnic diversity. The results show that the ter-ater serves as a medium for strengthening brotherhood and a means of building harmony. The Islamic values embodied in this tradition foster tolerance and maintain harmony among residents. Ter-ater has been proven to expand social networks and strengthen solidarity, making it a religious-cultural instrument that not only preserves local heritage but is also relevant in strengthening harmony and tolerance in a multicultural society